2021
DOI: 10.3390/ijerph18073743
|View full text |Cite
|
Sign up to set email alerts
|

Brief Mental Health Disorder Screening Questionnaires and Use with Public Safety Personnel: A Review

Abstract: Brief mental health disorder screening questionnaires (SQs) are used by psychiatrists, physicians, researchers, psychologists, and other mental health professionals and may provide an efficient method to guide clinicians to query symptom areas requiring further assessment. For example, annual screening has been used to help identify military personnel who may need help. Nearly half (44.5%) of Canadian public safety personnel (PSP) screen positive for one or more mental health disorder(s); as such, regular ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 79 publications
(162 reference statements)
0
11
0
Order By: Relevance
“…Brief mental health disorder screening tools have useful applications and are widely used by clinicians and researchers as they provide an efficient method to query symptom areas requiring further assessment or research. 75 They are, however, not a substitute for full diagnostic criteria. 76 Therefore, this study must be viewed in the light that we used brief screening tools as opposed to a full clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brief mental health disorder screening tools have useful applications and are widely used by clinicians and researchers as they provide an efficient method to query symptom areas requiring further assessment or research. 75 They are, however, not a substitute for full diagnostic criteria. 76 Therefore, this study must be viewed in the light that we used brief screening tools as opposed to a full clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
“…To address this, we used validated screening tools and analysis techniques that allowed for an assessment of ongoing stress and anxiety related specifically to the flood event (as distinct from anxiety arising from other causes). Brief mental health disorder screening tools have useful applications and are widely used by clinicians and researchers as they provide an efficient method to query symptom areas requiring further assessment or research 75. They are, however, not a substitute for full diagnostic criteria 76.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria of study participants were as follows: (1) must be compos mentis, (2) a Muslim to implement prayer and dhikr (the ritual formula of Sufi brotherhood recited devotionally in praise of Allah and as a means of attaining ecstatic experience [18]), (3) aged 18-64 years (young adults to older adults who can legally sign the informed concern) and diagnosed with T2DM, (4) with diabetes fatigue condition who have been screened using the Multidimensional Fatigue Inventory (MFI-20) questionnaire, (5) undergoing treatment for T2DM for at least 3 years; (6) ability to write and speak Bahasa (Indonesian national language) and Javanese (local language), and (7) willing and committed to participate in this research until completion. Respondents were excluded if they (1) experienced generalized anxiety disorder and major depressive disorder and have been screened using the Patient Health Questionnaire 4 [19,20], (2) had a hemoglobin level of <10 mg/dL, and (3) could not participate in the research process until completion. In the treatment group, during the intervention, seven of 50 respondents were lost to follow-up, and three discontinued (two worked in a different city and one moved to a different residence) from the study (Pucang Sewu = 20 respondents and Tanah Kalikedinding = 20 respondents).…”
Section: Setting and Samplementioning
confidence: 99%
“…Mental health awareness has been increasing for several years, and research has shown the effects of mental health disorders on individuals’ lives. 6 …”
Section: Introductionmentioning
confidence: 99%